The effects of acetazolamide on physiological variables among adolescents at high altitude - Govindasamy Balasekaran; Sarah Thompson; Visvasuresh Victor Govindaswamy; Yew Cheo Ng (Sport Sciences and Health Research)
Background: High altitude environments can cause a range of physiological changes in the body, and adolescents may be particularly vulnerable to the effects of altitude sickness. Acetazolamide has been shown to be an effective treatment for altitude sickness, but further research is needed to determine its impact on physiological variables among adolescents at high altitude. Aim: The aim of this study was to investigate the effects of acetazolamide in adolescents over 17 days at high altitude. Materials and Methods: Twenty-five healthy adolescents volunteered for this study and were randomly separated into control group (CG, n=12) and acetazolamide group (AG, n=13). AG took 250mg of acetazolamide. Resting Heart Rate (RHR) and Acute Mountain Sickness (AMS) using the Lake Louise questionnaire were measured each morning and afternoon during field testing; Resting Blood Pressure (RBP) was measured each afternoon. Pre- and post-blood samples (haemoglobin (Hb) and haematocrit (Hct)) were taken at sea level (SL) one week before departure and within 40 hours on return to SL. Results: Significant differences between groups for RHR on days 2, 3 and 5; systolic blood pressures for day 4 and 13 (P<0.05). No significant difference between groups for diastolic blood pressure, pre- and post-altitude for Hb, Hct and PV. AMS scores did not differ from the two groups except on morning of day 12 (P<0.05). Discussion and Conclusion: Results revealed that acetazolamide did not significantly induce changes to adolescents’ AMS scores and physiological changes. However, adolescents may consume acetazolamide to achieve lower RHR that may enable them to accommodate to HA, prolonging exercise in similar environments.